EVALUASI PROGRAM EKSTRAKURIKULER DAN KONTRIBUSINYA TERHADAP PENGEMBANGAN KARAKTER SISWA DI SDIT AL IZZAH SERANG - Muhammad Arifin Arifin; Hamdanah; Nuryati; Deden Hidayat; Epi Hasan Rifai; Siti Nurbani; Afdi Maulfianti; Dede Mulyati (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2025)
The research used is a mixed methods approach with a sequential explanatory design. The quantitative phase involved a survey with questionnaires administered to teachers and guardians to measure their perceptions of the implementation and benefits of extracurricular programs. Quantitative data were analyzed descriptively and inferentially. The qualitative stage was conducted through in-depth interviews with school officials, extracurricular supervising teachers, and student guardian representatives to explore more in-depth information regarding the experiences, challenges, and successes of the program in shaping student character. The quantitative research results showed a high level of satisfaction and positive perceptions of the extracurricular program from teachers and student guardians. Qualitative analysis reinforces these findings by revealing how various extracurricular activities such as scouting, arts, and sports provide opportunities for students to develop character values such as discipline, cooperation, responsibility, independence, and self-confidence. Further discussion elaborates on the factors that support the success of the program and provides recommendations for improving the implementation of extracurricular programs at SDIT Al Izzah Serang so that their contribution to students' character development becomes more optimal. Keywords: Program Evaluation, Extracurricular, Character,